PERANAN ANGGOTA KELOMPOK DALAM PENGEMBANGAN KELOMPOK TANI DI KELURAHAN LANSOT KECAMATAN TOMOHON SELATAN - Marsel R. P. Mege; Martha M. Sendow; Oktavianus Porajouw; Welson M. Wangke (Universitas Sam Ratulangi, 2014)
ABSTRACTMarsel Mege. The Role of Group Member in Developing Farmer Group in LansotVillage, South Tomohon Sub District. Under the guidance of Dra. Martha M.Sendow, MSi as Chairman, Ir. Octavian Porajouw, MS, and Ir. Welson M. Wangke,MS, as MembersThe objective of this research is to determine the role of group member indeveloping of farmer group.The data used is primary data obtained from interviewing all members ofMahsawasawangan and Pinaesaan farmer groups. The interviews are guided by a list ofquestions that had been prepared before. Sampling method used is census method. Thenumber of member of Pinaesaan farmer group are 10 people and farmer groupMahsawasawanganare 9 people . Data is analyzed descriptively and presents in tabularform.The research result showed that the role of Pinaesaan farmer group members wasmore active Pinaesaan than Mahsawasawangan farmer group member that could be seenfrom the level of attendance at the activities that had been done . Therefore, the role ofPinaesaan farmer groups more advanced and more developed than Masawasawanganfarmer group.For Mahsasawangan farmer group , the level of activity of members in eachactivity were less than 50 percent , perhaps due to the average age of the members wereover 60 Years and the capacity ofhuman resources were low because most of the memberswere graduated from primary school. so that the farmer groups Mahsawasawangan lessdeveloped compared with farmer groups Pinaesaan.